CT angiogram negative perimesencephalic subarachnoid hemorrhage: is a subsequent DSA necessary? A systematic review. (4th July 2019) - Mohan, Midhun; Islim, Abdurrahman; Dulhanty, Louise; Parry-Jones, Adrian; Patel, Hiren
Abstract : Background: Perimesencephalic subarachnoid hemorrhage (PMSAH) is a benign subtype with distinct clinical-radiologic features. Digital subtraction angiography (DSA) remains the gold standard investigation for exclusion of a macrovascular cause, although increasingly more clinicians rely solely on CT angiography (CTA). The primary aim of this systematic review was to evaluate the current literature regarding the negative predictive value of CTA. Methods: A systematic search in concordance with the PRISMA checklist was performed for studies published between 2000 and 2018. Studies with ≥10 adult patients diagnosed on a non-contrast brain CT with a PMSAH, who underwent a negative CTA and were subsequently subject to a DSA, were included. Simple pooled analysis was performed to inform the negative predictive value (95% CI) of CTA and the risk of DSA- and CTA-related complications. Results: Eighteen studies (669 patients) were included. All patients were subject to at least one DSA, the first one mostly performed within 24 hours of CTA (68.6%). 144 patients (21.5%) underwent a second DSA and a third repeat DSA was performed in one patient. The overall negative predictive value of CTA was 99.0% (95% CI 97.8% to 99.5%). The risk of complications following DSA and CTA were 1.35% (3/222) and 0% (0/41), respectively. Conclusions: Undertaking a DSA after a negative CTA may not add any further diagnostic value in patients with PMSAH and may lead to net harm. This observation needs to be validated in a large-scale prospective multicenter study with complete case ascertainment and robust data on CTA and DSA complications.